KAJIAN YURIDIS ATAS KEJAHATAN PASAR MODAL DI BURSA EFEK INDONESIA MENURUT UU NO. 8 TAHUN 1995 TENTANG PASAR MODAL - Bismar Nasution; T. Keizerina Devi (TRANSPARENCY, 2014)
Nowdays, capital market plays the important rules in this modern economic era which is supported by the capital market’s crime happened, that is why it needs to be discussed further. The issues that will be raised by  the author is the categories of capital market included the legal base, the solution of capital market’s crimes, the sanction application those are in the Law No. 8 years 1995 to solve the case of capital market’s crimes. The research method used by the author was a literature research, which is the juridical normative that aims to describe in a systematic, factual and accurate to state the object of a study by research based on normative legal provision. Research source used is sourced from secondary data. This research result proves that there are four categories of capital market’s crime happened in capital market among others are fraud explained in the article 90 UUPM, market manipulation fraud explained in the article 91 and 92 UUPM, insider trading fraud explained in the article 95-99 UUPM dan miss leding information fraud explained in the article 80,81,93 UUPM. The way to handle capital market’s crimes according the PP 46 Years 1995 and UUPM are OJK made a team which consist of the duty of investigation, reporting, the given of administration sanction, and the further action by the prosecutor if there is any crime. All the sanctions that are given by Bapepam for every case that are happened in BEI likes the fraud case of PT Sarijaya Permana Sekuritas, market manipulation case of PT Dharma Samudra Fishing Industries Tbk, insider trading case of PT PGN, miss leading information case of PT Bank Lippo Tbk which is reviewed by the Law No.8 Years 1995 is very weak because the sanction terminates to the administrative sanction.